EVALUATION OF DISTANCE LEARNING POLICY DURING THE COVID-19 PANDEMIC IN ELEMENTARY SCHOOL - Gilang Ramadhan; Luthfiah Andriliani; Ina Magdalena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
This study aims to determine the implementation of learning evaluation at SDN Poris Pelawad 1, Tangerang City. The research method used is a qualitative method with descriptive data exposure. Data collection techniques using interviews, observation, and documentation. Sources of data collection were obtained from sources/informants and from the research site. The results of this study are that the evaluation of distance learning policies at SDN Poris Pelawad 1 has been carried out quite well. This school has used the 2013 curriculum, so for its evaluation it must meet three domains, namely the realm of knowledge, attitudes and skills. This study uses an interview method to one of the teachers of SD Negeri Poris Pelawad 1. The interviews were conducted directly/offline by approaching the resource persons.